2017
DOI: 10.4274/balkanmedj.2017.1160
|View full text |Cite
|
Sign up to set email alerts
|

Translational Functional Neuroimaging in the Explanation of Depression

Abstract: Translation as a notion and procedure is deeply embodied in medical science and education. Translation includes the possibility to translate data across disciplines to improve diagnosis and treatment procedures. The evidence accumulated using translation serves as a vehicle for reification of medical diagnoses. There are promising, established post hoc correlations between the different types of clinical tools (interviews and inventories) and neuroscience. The various measures represent statistical correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 105 publications
(105 reference statements)
0
15
0
Order By: Relevance
“…The robustness of the results was tested to prove the regions we found was stability and repeatability ( Supplementary Figures S2, S3). In the studies pretend to explore the neural mechanism about MCI, AD or depression, these regions also have been mentioned (Langenecker et al, 2007; Alexopoulos et al, 2008;Yao et al, 2009;Lee et al, 2012;Xie et al, 2012;Zhang et al, 2012;Rizio and Dennis, 2014;Guo et al, 2016;Stoyanov et al, 2017;Kandilarova et al, 2018;Yang et al, 2018;Kandilarova et al, 2019). These brain regions may be the proof of a possible shared pathophysiology in both depression and MCI (Yao et al, 2009;Zhang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The robustness of the results was tested to prove the regions we found was stability and repeatability ( Supplementary Figures S2, S3). In the studies pretend to explore the neural mechanism about MCI, AD or depression, these regions also have been mentioned (Langenecker et al, 2007; Alexopoulos et al, 2008;Yao et al, 2009;Lee et al, 2012;Xie et al, 2012;Zhang et al, 2012;Rizio and Dennis, 2014;Guo et al, 2016;Stoyanov et al, 2017;Kandilarova et al, 2018;Yang et al, 2018;Kandilarova et al, 2019). These brain regions may be the proof of a possible shared pathophysiology in both depression and MCI (Yao et al, 2009;Zhang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…IBA involves dynamic neural and metabolic activities, it is activity and plays a pivotal role in brain function (Dai and He, 2014;Raichle, 2015). These methods have been widely used to evaluate the IBA of neurological disorders or neuropsychiatric disorders, such as AD, depression, and MCI (Yao et al, 2009;Zhang et al, 2012;Guo et al, 2016;Wee et al, 2016;Stoyanov et al, 2017;Zhang et al, 2017;Kandilarova et al, 2018;Yang et al, 2018;Liu et al, 2019). Furthermore, evidence indicated that once brain got an internal or external stimuli, it could respond by dynamic integration or adjustment over multiple time scales (Hutchison et al, 2013;Bassett and Sporns, 2017;Yan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Functional magnetic resonance imaging (fMRI) with its widening availability, non‐invasive nature, relatively low cost, and good spatial resolution represents an important method for indirect measurement of task‐associated brain activity and provides an excellent example of translational neuroscience that bridges knowledge across disciplines in medicine …”
Section: Introductionmentioning
confidence: 99%
“…Functional magnetic resonance imaging (fMRI) with its widening availability, non-invasive nature, relatively low cost, and good spatial resolution represents an important method for indirect measurement of task-associated brain activity and provides an excellent example of translational neuroscience that bridges knowledge across disciplines in medicine. 7 fMRI is used widely in childhood and adolescence in studies of reorganization after early brain injuries and thus contributes to the translation of neurobiological mechanisms to clinical practice, helping to individualize the therapeutic plan of patients with developmental disorders. 4,7,8 UCP is an appealing model for the study of brain plasticity by fMRI for several reasons:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation